( | 1 | + | x | ) | ÷ | ( | 1 | + | 2 100 | ) | − | 1 | = | 10 100 |
Multiply both sides of the equation by: | ( | 1 | + | 2 100 | ) |
( | 1 | + | x | ) | − | 1 | ( | 1 | + | 2 100 | ) | = | 10 100 | ( | 1 | + | 2 100 | ) |
1 | + | x | − | 1 | ( | 1 | + | 2 100 | ) | = | 10 100 | ( | 1 | + | 2 100 | ) |
1 | + | x | − | 1 | ( | 1 | + | 2 100 | ) | = | 10 100 | × | 1 | + | 10 100 | × | 2 100 |
1 | + | x | − | 1 | ( | 1 | + | 2 100 | ) | = | 1 10 | + | 1 500 |
1 | + | x | − | 1 | ( | 1 | + | 2 100 | ) | = | 51 500 |
1 | + | x | − | 1 | × | 1 | − | 1 | × | 2 100 | = | 51 500 |
1 | + | x | − | 1 | − | 1 50 | = | 51 500 |
- | 1 50 | + | x | = | 51 500 |
x | = | 51 500 | + | 1 50 |
x | = | 61 500 |